ISOLATION AND INVESTIGATION OF PHYTOCHEMICALS AND PHARMACOLOGICAL SCREENING OF TAGETES ERECTA L. LEAVES EXTRACT - Jayavant, Thorat Kranti (Asian Journal of Pharmaceutical Research and Development, 2018)
Extraction and isolation of plant constituents plays an important role as a therapeutic remedy. Isolation of active plant constituents helps in developing lead molecule in drug development process. Aim of present study is to extract, isolate plant constituents and spectral and pharmacological investigation. The major advantage of herbal drugs to synthetic drugs is that they produce more therapeutic effect and fewer side effects. Herbal drugs also have potential in drug development by generating a lead molecule which helps in designing of synthetic drugs. Tagetes species belonging to family Asteraceae, are most common in plant kingdom, which is used in different areas like cosmetic preparation, medicines as well as it is most commonly used as ornamentals. Flowers are mainly used for all these purposes by using extraction process. Tagetes species contains mainly lutien such as carotenoids or xanthophylls containing two cyclic end groups and basic C-40 isoprene unit. The leaves are reported to possess wound healing, antiulcer, muscular pain relief activities10. The basic criteria of present work are to isolate the active plant constituents from these plants and to avail about its anticancer activity on cancer cell line